Difficult Dreams - Sara Carpenter; Danielle Gardiner Milln; Joshuha Connauton; Laura Woodman; Meshia G-K Brown; Wilson Javier Mora Rivera; Fatemeh Mirikarbasaki; Arina Ehsan (Sisyphus, 2024)
Human capital theory (HCT) has moved from a core tenet of neoclassical economic theory to a normative and prescriptive policy position that guides our understanding of economic growth across multiple scales, from the individual to the national. In this paper, a diverse group of graduate students interrogate their experiences of accumulating and realising ‘human capital.’ They argue that HCT holds at its centre an abstract and falsely universal subject that obscures how transnational relations of patriarchy, race, and coloniality constitute class relations and thus create a reality in which investments in human capital cannot be realised by all. This paper further elaborates how this group of adult learners developed an understanding of class as a socially constituted relation within capital and thus foregrounds the need for adult educators to work from a more nuanced articulation of class that recognizes relationality with other forms of oppression.